Incidence Rate and Risk Factor Analysis of Asphyxia Neonatorum - Intan Kumalasari; Indah Dewi Ridawati; Maliha Amin; Herawati Jaya; Ismar Agustin; Zizke Rusella (Journal of Health Science Community, 2022)
Asphyxia neonatorum is still the third cause of death for newborns in the first week of life. Failure to breathe spontaneously and regularly after birth if not handled properly will be fatal for the baby's life. The purpose of this study was to determine the risk factors and incidence of asphyxia neonatorum. This study uses an analytical survey with a cross sectional approach, using secondary data from the medical record installation of Muhamadiyah Hospital Palembang for the period 1 Sept to 1 Oct 2016 with a total sampling technique of 156 births. statistical analysis using chi-square. The results of the analysis of the incidence of asphyxia neonatorum was 8.3%. There was a significant relationship between amniotic fluid mixed with meconium (p=0,000;OR=21,719) and prolonged second stage (p=0,002;OR=42,600) and asphyxia neonatorum. Early detection through regular antenatal examinations can minimize risk factors and the incidence of asphyxia neonatorum.